Synthesis of Ofornine mimics from natural product l-vasicine as anti-hypertensive agents. Issue 4 (15th February 2017) - Aga, Mushtaq A.; Rayees, Sheikh; Rouf, Abdul; Kumar, Brijesh; Sharma, Anjna; Nagaraju, P.V.V.S.; Singh, Gurdarshan; Taneja, Subhash C.
Graphical abstract: A process for the synthesis of a library of vasodilator Ofornine mimics is reported from l -vasicine which was isolated from Adhatoda vasica . The synthesized analogs were studied for structure-activity relationship and in vivo screening for anti-hypertensive action in Wistar rats. Most of the analogs were observed to possess anti-hypertensive effect; however, the duration of the effect was variable and mostly transient. Analog ( S )-(3-hydroxypyrrolidin-1-yl)(2-(pyridin-4-ylamino)phenyl)methanone (8 ) showed a significant decrease in blood pressure in a dose dependent manner whose maximal response lowered to 79.29 ± 4.26 mmHg of SBP and 62.55 ± 2.9 of DBP at 10 mg/kg intravenous dose. Structure–activity studies reveal that amide, hydroxyl and pyridine ring plays important role in the activity. Abstract: We report the chemical synthesis of Ofornine mimics from l -vasicine, structure-activity relationship studies and their in vivo screening for anti-hypertensive action in Wistar rats. It was observed that most of the analogs possessed anti-hypertensive effect; however, the duration of the effect was variable and mostly transient. The results demonstrated that the analogs12, 13, 14, 15, and16 showed a sharp and significant decrease in systolic and diastolic blood pressure for 30–60 min after intravenous administration. Analog ( S )-(3-hydroxypyrrolidin-1-yl)(2-(pyridin-4-ylamino)phenyl)methanone (8 ) showed a significant decrease in blood pressure in a dose dependent manner whose maximal response lowered to 79.29 ± 4.26 mmHg of SBP and 62.55 ± 2.9 of DBP at 10 mg/kg intravenous dose. Further, the significant anti-hypertensive effect of8 lasted for about 2.5 h at 10 mg/kg dose. We also evaluated the acute toxicity of the analog8 as per the OECD guidelines and the compound was found to be safe up to the dose of 2000 mg/kg body weight. These preclinical findings suggest that the analog8 could be considered as a promising lead and a durable anti-hypertensive drug candidate and deserves further investigation. The SAR studies clearly showed that the amide, hydroxyl and pyridine ring plays important role in showing the activity.